Issue Information TOC. Issue 1 (22nd December 2019) - Unknown
Abstract : Cover : In Liu et al. (https://doi.org/10.1002/cpph.69 ), the image shows a comparison between conventional manual patch clamp and automated electrophysiology. (A ) Schematic of manual patch clamp recording (left panel) under whole‐cell configuration. A single cell is recorded using a glass recording pipette. Compounds can be applied to the extracellular solution (blue), whereas the artificial intracellular solution (green) is contained in the pipette. Right panel: voltage pulse protocol and representative transient inward Nav1.7 channel current. (B ) Schematic of planar array–based automated electrophysiology experiment. A single cell is recorded through a micropore in a single well (upper left) from a chip containing 384 wells (upper right). Both extracellular (blue) and intracellular (green) solutions can be changed by perfusion. Lower panel: representative result from one Syncropatch run. Wells were color coded based on seal resistance. Resistance, cells: green, >0.5 GΩ, 350/384; blue, 100 to 500 MΩ, 30/384; white, <100 MΩ, 4/384. Current traces within each well were autoscaled for maximum display.